ANALISIS SALURAN DISTRIBUSI MOBIL PADA PT. ELIT BURSA CABANG KISARAN - Mursalati Urfa; Putri Ramadhani; Muhammad Andre Wardhana; Eri Eri; Suhairi Suhairi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the distribution channel of cars at PT. Elite Exchange Branch Range. Types of Research This research is a descriptive type of research. A qualitative approach is obtained, including information about PT. Elite Bursa Kisaran Branch, in the form of an overview of the history of the establishment of PT. Elite Bursa Branch Range, organizational structure, and information on distribution channels at PT. Elite Exchange Branch Range, research time will be adjusted. The population taken is employees of PT. Elite Exchange Branch Range. Informants The informants used are the Branch Head, Vehicle Warehouse Coordinator / PDI, three Sales PT. Elite Bursa Branch of Kisaran, and 2 Consumers of PT. Elite Exchange Branch Range. Sampling Technique This research uses the Snowball Sampling method: The technique of determining the sample which is initially small in number then enlarges. In this study using data collection techniques that can be done, namely interviews. Analytical Methods The analytical method used in this research is a qualitative approach. The results of this study are based on the results of research on Abadi PT. Elite Exchange Branch Range on the analysis of car distribution channels. So the author can conclude that the distribution channel used by PT. Elite Exchange Branch Range is to use level zero distribution channels and level one distribution channels.